Visual Outcome of Vision Threatening Diabetic Retinopathy after Various Treatment Modalities - Muhammad Faisal Fahin Seema N. Mumtaz, Sidra Shakil, M. Saleh Memon, P. S. Mahar, Abdul Fattah Memon (Pakistan Journal of Ophthalmology, 2019)
Purpose: To determine the visual outcome of laser treatment and intra-vitreal Avastin (Bevacizumab) injection as mono-therapy or combined, in patients with Vision Threatening Diabetic Retinopathy (VTDR). Study Design: Quasi Experimental study with non-probability convenient sampling. Place & Duration of Study: Isra Postgraduate Institute of Ophthalmology, Al-Ibrahim Eye Hospital, Karachi from January 2016 to December 2017. Material & Methods: Patients with Diabetic retinopathy (DR) were graded according to International clinical diabetic retinopathy & macular edema disease severity scale. Patients with VTDR were offered Laser therapy, intra-vitreal Avastin injection or both. Results: VTDR was witnessed in 586 patients out of 1988 patients with DR. Out of which 108 had Proliferative Diabetic Retinopathy (PDR), 382 had clinically significant macular edema (CSME) and 96 had Advanced Diabetic Eye Disease (ADED). Laser was done in 78 eyes, intravitreal Avastin was given in 340 eyes and combined laser and Avastin were given in 35 eyes. When visual outcome was correlated with treatment modalities, improvement was found in 248 eyes, deterioration in 34 eyes and stabilization in 58 eyes of Avastin group, whereas improvement was seen in 45 eyes, deterioration in 15 eyes and stabilization in 18 eyes of laser group. In combined treatment group, improvement was witnessed in 23 eyes, deterioration in 4 eyes and stabilization in 8 eyes. Conclusions: Visual outcome of Avastin alone or combined with laser was found to be better than laser treatment alone in stabilizing the visual acuity in patients with vision threatening diabetic retinopathy. Keywords: Bevacizumab, Laser, Intra vitreal Injection, Avastin.